(3QSGFd GdTjN GdEeGe YHO GdYRjR Hf NdjaIs - (3YHO GdYRjR Hf NdjaI GdbSfWjfjs
(3ChdgG (B:s
(3GdMeO ddg aGWQ GdSehGJ hGdCQV LGYd GdedGFcI QSdkG Chdi CLfMI eKfi hKdGK hQHGY s
(3BNQgG (B:s
(3hdG fSCd eKd GdeZaQI s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(258) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs